Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/echo.13426
|View full text |Cite
|
Sign up to set email alerts
|

Apical left ventricular myocardial dysfunction is an early feature of cardiac involvement in myotonic dystrophy type 1

Abstract: Despite preserved LVEF, DM1 patients exhibited significantly altered LV GLS, particularly at the apex, as compared with controls. The detection of impaired myocardial deformation at early stages of the disease might help to screen high-risk patients who need closer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…GLS was similar to or slightly higher than in previous reports using different methodology 26,27 . Particularly in apical wall regions of the LV, we detected slightly decreased myocardial strain in DM patients, which did not significantly affect global longitudinal systolic strain (GLS) or LV EF, similar to previous findings 28 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…GLS was similar to or slightly higher than in previous reports using different methodology 26,27 . Particularly in apical wall regions of the LV, we detected slightly decreased myocardial strain in DM patients, which did not significantly affect global longitudinal systolic strain (GLS) or LV EF, similar to previous findings 28 …”
Section: Discussionsupporting
confidence: 90%
“…26,27 Particularly in apical wall regions of the LV, we detected slightly decreased myocardial strain in DM patients, which did not significantly affect global longitudinal systolic strain (GLS) or LV EF, similar to previous findings. 28 Non-ischaemic LGE is a cMR marker of regional interstitial fibrosis. In our DM cohort, only two patients (6.5%) had non-ischaemic LGE, which is lower than in previous studies that reported a prevalence of myocardial fibrosis in myotonic dystrophy between 14% and 40%.…”
mentioning
confidence: 99%
“…Despite more and more studies in the literature, cardiac management of asymptomatic DM1 is not codified and identification of tools enabling to predict these complications is crucial (Lau et al, 2015). Several parameters have been described as predictors of cardiovascular events: age, left bundle branch block, syncope, atrial fibrillation, longitudinal strain, left ventricular ejection fraction (Bhakta et al, 2010;Garcia, Labarre, et al, 2017;Garcia, Rehman, et al, 2017;Lau et al, 2015;Wahbi et al, 2017). Nevertheless, the relevancy of 24-hour holter ECG, which is currently recommended, has never been assessed (Lau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that 30% of deaths are caused by arrhythmias, most of the studies seem to agree on the difficulty of predicting cardiac disorders in DM1 patients (Pelargonio et al, 2002). Several predictors of cardiovascular events have been described but DM1 patient follow-up is not standardized (Bhakta, Groh, Shen, Pascuzzi, & Groh, 2010;Garcia, Labarre, et al, 2017;Garcia, Rehman, et al, 2017;Lau, Sy, Corbett, & Kritharides, 2015;Wahbi et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Twenty-four studies assessed the cardiac muscle strength indirectly [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][104][105][106]112,113].…”
Section: Cardiac Muscle Strengthmentioning
confidence: 99%